Plasma protein binding limits the blood brain barrier permeation of the pyrethroid insecticide, deltamethrin. (27th May 2016) - Amaraneni, Manoj; Sharma, Anshika; Pang, Jing; Muralidhara, Srinivasa; Cummings, Brian S.; White, Catherine A.; Bruckner, James V.; Zastre, Jason
Highlights: Deltamethrin (DLM) is not a P-glycoprotein substrate or inhibitor. The extent of DLM permeation into the brain is dependent on protein binding. Transport of DLM is linear/passive at physiological albumin concentrations. Abstract: Previous pharmacokinetic studies of deltamethrin (DLM) have revealed that brain levels of this highly lipophilic pyrethroid insecticide are only 15–20% of plasma levels. Experiments were performed to assess determinants limiting CNS access including plasma protein binding and the efflux transporter, P-gp. A human brain microvascular endothelial cell line, hCMEC/D3, was utilized as a model in vitro system to evaluate blood-brain barrier (BBB) permeation. Incubation of DLM with a series of human serum albumin (HSA) concentrations showed that unbound (fu ) DLM ranged from 80% with 0.01% HSA to ∼20% at the physiologically-relevant 4% HSA. A positive correlation (R = 0.987) was seen between fu and cellular uptake. Concentration-dependent uptake of DLM in 0.01% HSA was non-linear and was reduced at 4 °C and by the P-gp inhibitor cyclosporine (CSA), indicative of a specific transport process. Cellular accumulation of [ 3 H]-paclitaxel, a P-glycoprotein (P-gp) substrate, was increased by CSA but not by DLM, suggesting that DLM is neither a substrate nor an inhibitor of P-gp. The concentration-dependent uptake of DLM from 4% HSA was linear and not significantly impacted by temperature or CSA. In situ brain perfusion studies monitoring brain association of DLM at 0.01% and 4% HSA confirmed the aforementioned in vitro findings. This study demonstrates that brain uptake of DLM under normal physiological conditions appears to be a passive, non-saturable process, limited by the high protein binding of the pyrethroid.